Localization of an Autonomous Personnel Carrying Vehicle in Indoor Environments - Altug, Erdinc; Gelbal, Şükrü Yaren; Kececi, Emin Faruk; Gültekin, Mehmet Kabil (Association for Computing Machinery acmhelp@acm.org, 2017)
There is an emerging need of intelligent vehicles on indoor environments such as university campuses, airports or shopping malls. These intelligent vehicles can help elderly, disabled, or people with heavy luggage. This paper describes an intelligent vehicle that can be used indoor as well as outdoor areas for this purpose. Finding the exact location for indoor robots is not an easy task, since Global Positioning System (GPS) is not available indoors. In this work onboard sensors such as motor encoder and steering-wheel encoder were used to obtain localization estimates. The errors are determined to be low even when the vehicle travels long distances. © 2017 Elsevier B.V., All rights reserved.
Keywords: Autonomous; Driverless Vehicles; Obstacle Avoidance; Collision Avoidance; Global Positioning System; Indoor Positioning Systems; Intelligent Vehicle Highway Systems; Signal Encoding; Autonomous; Driverless; Indoor Environment; Motor Encoders; On-Board Sensors; Steering Wheel; University Campus; Vehicle Travels; Vehicles